Valve behavior of the European flat oyster Ostrea edulis and associated underwater sound and temperature data, recorded during a 18-month in situ experiment in Helgoland, Germany - Alexandre Le Moal; Laura Payton; Yannick Geerebaert; Bettina Meyer; Bernadette Pogoda; Damien Tran (PANGAEA, 2025)
Once widespread across European coasts, the native flat oyster Ostrea edulis has now disappeared from most of its historical range and is officially recognized as threatened. As a key ecological engineer, this species supports biodiversity by filtering water, stabilizing sediments, and providing complex reef habitats. Understanding and evaluating its behavior and biological rhythms in a natural environment before reintroduction, and how it responds to natural geophysical cycles, is essential to support effective restoration strategies. However, current knowledge on O. edulis remains limited, with most studies focusing primarily on reproduction under aquaculture or laboratory conditions. To help fill this gap, we conducted a 18-month in situ study to assess the valve behavior of Ostrea edulis in the field. The experiment took place at the Margate site (54.19°, 7.88°) near the island of Helgoland (Germany) from the 11th of March 2023 to the 31st of August 2024. The experimental setup consisted of 16 oysters disposed on individual cages in a customized oyster basket placed on a lander, a metallic structure immersed at 10m depth. Their valve behavior was continuously measured during 18 months using a High-Frequency Non-Invasive (HFNI) valvometer biosensor (Tran et al. 2023; Le Moal et al. 2023 for further details). Briefly, a pair of lightweight electrodes (<100 mg) was glued on each half-shell of each oyster and was linked to the HFNI valvometer by a flexible wire, allowing undisturbed oyster valve movement. An electromagnetic field was generated between the electrodes, allowing the measurement of the distance between each oyster extquotesingles valve in continuous mode. In addition to the oyster behavior, environmental parameters were continuously measured underwater by the HFNI valvometer biosensor during the experiment, such as temperature and sound pressure magnitude. This compilation of datasets gives an overview of environmental parameters and behavioral data collected during this experiment.